PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR K3LH SISWA KELAS X TKP SMK NEGERI 2 MEDAN - Zulkifli Matondang; Elza Agustina Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model and learning motivation on the K3LH (Occupational Health, Safety, and Environment) learning outcomes of Grade X TKP students at SMK Negeri 2 Medan. The research sample consisted of two classes—X TKP 2 (taught using the CTL model) and X TKP 1 (taught using the Direct Instruction/DI model)—with 34 students in each. A quasi-experimental method with a 2×2 factorial design was employed, comprising pre-test, instruction, and post-test stages. The research instruments underwent testing for validity, reliability, difficulty level, and discriminatory power. Homogeneity test results indicated that both groups originated from a homogeneous population (F-calculated = 1.671 < F-table = 7.815). A two-way ANOVA revealed significant differences in learning outcomes between students taught via the CTL and DI models (F-calculated = 10.55 > F-table = 3.99) and between students with high and low learning motivation (F-calculated = 24.77 > F-table = 3.99). However, no interaction effect was found between the learning model and learning motivation regarding learning outcomes (F-calculated = 3.60 < F-table = 3.99). Thus, the CTL learning model and learning motivation influence students' K3LH learning outcomes, offering a consideration for teachers and schools aiming to improve academic performance.